Upaya Meningkatkan Hasil Belajar Bahasa Indonesia Materi Menulis Puisi Bebas melalui Penggunaan Model Pembelajaran Picture and Picture pada Siswa Kelas XI TKJ-1 SMK Negeri 2 Karang Baru Kabupaten Aceh Tamiang - Ash Habibi (Multiverse: Open Multidisciplinary Journal, 2022)
The objectives of this study are: To Improve Learning Outcomes Indonesian Free Poetry Writing Material for Class XI TKJ-1 Students of SMK Negeri 2 Karang Baru Aceh Tamiang Regency Through the Use of Picture and Picture Learning Models. This study used action research as many as two cycles of 4 meetings. Every te cycle. From the results of analysts, it was found that student learning achievement increased, namely cycle I of the first meeting (60%), the second meeting (65%), and cycle II of the first meeting (80%), the second meeting (90%). from this research are: (1)"Through the Use of Picture and Picture Learning Models, it can Improve Learning Outcomes Indonesian Free Poetry Writing Material for Class XI TKJ-1 Students of SMK Negeri 2 Karang Baru, Aceh Tamiang Regency". (2) The improvement results are characterized by the occurrence of learning completion, namely in the initial condition of students who are completed only 30% with an average score of 8, in the first cycle the first meeting increases to 60% with an average score of 60, cycle I of the second meeting increases to 65% with an average score of 65. In cycle II of the first meeting, the student's learning completion was 80% with an average score of 75 and in the second cycle of the second meeting, student learning outcomes were declared complete, namely the student's learning completion became 90%.